Changes in corneal biomechanics in patients with glaucoma: a systematic review and meta-analysis - Xinru Li (BMC Ophthalmology, 2024)
Abstract Introduction Corneal biomechanics has been implicated in a variety of ocular diseases. The purpose of this study was to evaluate the relationship between the glaucoma and corneal biomechanical properties, and exploring the value of corneal biomechanics in the diagnosis and follow-up of glaucoma diseases. Methods We searched studies in PubMed, EMBASE, Web of Science and clinicaltrials.gov., as of October 8, 2022. Only English studies were included, without publication time limit. We also searched the reference lists of published reviews. This meta-analysis was conducted with random-effects models, we used mean difference(MD) to evaluate the outcome, and the heterogeneity was assessed with the I2 statistic. Subgroup analyses were performed under the appearance of high heterogeneity. We used 11 items to describe the characteristics of included studies, publication bias was performed through the Egger’s test. The quality assessment were evaluated by Newcastle–Ottawa Scale(NOS) items. Results A total of 27 eligible studies were identified for data synthesis and assessment. The result of meta-analysis showed that in the comparison of included indicators, the corneal biomechanics values of glaucoma patients were statistically lower than those of normal subjects in a similar age range. The covered indicators included central corneal thickness(CCT) (MD = -8.34, 95% CI: [-11.74, -4.94]; P < 0.001), corneal hysteresis(CH)(MD = -1.54, 95% CI: [-1.88, -1.20]; P < 0.001), corneal resistance factor(CRF)( MD = -0.82, 95% CI: [-1.21, -0.44]; P < 0.001), and intraocular pressure(IOP)( corneal-compensated intraocular pressure (IOPcc): MD = 2.45, 95% CI: [1.51, 3.38]; P < 0.001); Goldmann-correlated intraocular pressure (IOPg): MD = 1.30, 95% CI: [0.41, 2.20]; P = 0.004), they all showed statistical difference. While the value of axial length(AL) did not show statistically different(MD = 0.13, 95% CI: [-0.24, 0.50]; P = 0.48). Conclusion Corneal biomechanics are associated with glaucoma. The findings can be useful for the design of glaucoma screening, treatment and prognosis.